The Effect of Budgeting Performance on Economic Growt and Its Impact on Poverty Level - Bonifasia Elita Bharanti (Universitas Cenderawasih, 2019)
Papua has been one of the provinces in Indonesia which is of the central government’s concern. The government, through Special Autonomy running for 15 years, has disbursed Rp 59.51 trillion to Papua province with anexpectation that all funds are used for development. Each regency and city receives 80% of the special autonomy fund, which is an addition to provincial APBD fund. This large funding should be used to improve the welfare of the people, that is the use of budgets that have an impact on economic growth and the decline of poverty levels in regencies and city throughout the province of Papua. The aim of this study to analyse the direct effect of budgeting performance on economic growth and indirect influence on poverty level. The scope of the study area covers the regencies of Merauke, Jayapura, Jayawijaya, Biak, Nabire, Yapen Islands and Jayapura City. This study utilises data of the year 2010-2016 and it is analyzed using multiple regression. Hypothesis testing is done by T- and F-Tests. The results showed that partially budgeting performance (effectiveness, efficiency and independence) have positive yet insignificant effect on economic growth, while simultaneously it exhibits positive and significant impacton the economic growth. However, the economic growth is negatively insignificant to poverty, and does not mediate the effect of budgeting performance on poverty levels.